CARDIOVASCULAR EVENT RISK REDUCTION WITH MEDICINES: DATA OF EVIDENCE BASED MEDICINE AND RECOMMENDATIONS TO PRACTITIONERS - S. Y. Martsevich (Столичная издательская компания, 2016)
Cardiovascular event risk reduction with medicines is discussed in the article. The role of randomized controlled trials is emphasized for estimation of therapy effects.